GÊNERO, CORPO E @TIVISMOS - do Prado, Vagner Matias (Nuances: estudos sobre Educação, 2014)
Resenha livre da obra SOUZA, L. L.; GALINDO, D.; BERTOLINE, V. (Org.). Gênero, Corpo e @tivismos. Cuiabá: UFMT, 2012.